2017
DOI: 10.1002/pssa.201700685
|View full text |Cite
|
Sign up to set email alerts
|

Influence of PE‐ALD of GaP on the Silicon Wafers Quality

Abstract: An attractive method of low‐temperature plasma‐enhanced atomic layer deposition (PE‐ALD) of GaP on silicon wafer was recently proposed. In the present paper, the influence of the growth process on the quality of silicon wafers is explored by space charge capacitance techniques, C–V profiling and deep level transient spectroscopy (DLTS). No DLTS peak is observed for PE‐ALD GaP deposited onto n‐type wafer, meaning that the defect concentration is very low (less than 1 × 1012 cm−3) and that the growth process doe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…To investigate the defects properties in the silicon substrates after dry etching, the Schottky diode structures were fabricated. [30] The same bottom ohmic contact with the (n)a-Si:H layer as for the solar cell structures described previously was formed on the bottom side. To fabricate Schottky contact, 50 nm of Au was thermally evaporated on the top side using free mask with hole diameters of 0.5 and 1 mm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate the defects properties in the silicon substrates after dry etching, the Schottky diode structures were fabricated. [30] The same bottom ohmic contact with the (n)a-Si:H layer as for the solar cell structures described previously was formed on the bottom side. To fabricate Schottky contact, 50 nm of Au was thermally evaporated on the top side using free mask with hole diameters of 0.5 and 1 mm.…”
Section: Methodsmentioning
confidence: 99%
“…To investigate the defects properties in the silicon substrates after dry etching, the Schottky diode structures were fabricated . The same bottom ohmic contact with the (n)a‐Si:H layer as for the solar cell structures described previously was formed on the bottom side.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand hydrogen plasma could provide acceptor de‐activation in B doped p‐type Si and even damage the Si surface . Our previous study demonstrated that no significant influence of the growth process on the volume properties of silicon wafers could be observed by space charge capacitance techniques . However, to our knowledge the interface properties of GaP/Si heterojunctions formed by low temperature plasma‐assisted technique were not studied so far.…”
Section: Introductionmentioning
confidence: 92%